Diagnostic and prognostic utility of tissue factor for severe sepsis and sepsis-induced acute lung injury - Xue, Mingming; Sun, Zhan; Shao, Mian; Yin, Jun; Deng, Zhi; Zhang, Jin; Xing, Lingyu; Yang, Xiaoliang; Chen, Bin; Dong, Zhimin; Han, Yi; Sun, Si; et al. (Journal of translational medicine, 2015)
Tissue factor (TF) and tissue factor pathway inhibitor (TFPI) play a central role in the endothelial permeability regulation and dysfunction, which is associated with the development of sepsis and acute lung injury/acute respiratory distress syndrome (ALI/ARDS). The aim of this study is to assess the diagnostic and prognostic values of TF and TFPI in patients with sepsis and sepsis-induced ARDS. A total of 62 patients with sepsis, 167 patients with severe sepsis and 32 healthy volunteers were enrolled in this prospective observational study. TF and TFPI levels were measured by enzyme-linked immunosorbent assay (ELISA). Patients with sepsis-induced ARDS showed significantly higher median levels of TF compared with patients without ARDS (1425.5 (1019.9 to 2595.2) pg/ml vs 916.2 (724.1 to 1618.2) pg/ml, P < 0.001), and compared with sepsis patients (943.5 (786.4 to 992.4) pg/ml, P < 0.001) on the day of admission. However, there was no significant difference between sepsis patients and healthy subjects, or between septic shock and non-septic shock patients (P > 0.05). The AUC of TF for the diagnosis of sepsis-induced ARDS was 0.749 (95% confidence interval (CI) 0.675-0.822). Plasma TF levels in the non-survivors of severe sepsis were significantly higher than those of survivors (1618.6 (1017.1 to 2900.8) pg/ml vs. 979.9 (757.2 to 1645.5) pg/ml, P < 0.001), and multivariate logistic regression showed the plasma value of TF was the independent predictor for 30-day mortality in patients with severe sepsis (P = 0.0022, odds ratio (OR) = 1.41, 95% CI 1.24-1.69). The AUC of TF for predicting 30-day mortality in severe sepsis patients was 0.718 (95% CI 0.641-0.794). However, there was no significant difference in the plasma TFPI values among the healthy control, sepsis and severe sepsis groups (P > 0.05). Our data showed that tissue factor is a valuable diagnostic biomarker for the diagnosis of sepsis-induced ARDS. Moreover, tissue factor is a strong prognostic marker for short-term mortality in severe sepsis and sepsis-induced ARDS patients.